Empowering Heritage Tourism Communities through Foreign Language Capacity Building: Evidence from a Cultural Institution in Indonesia - Yeni Artanti; Ashadi Ashadi; Susana Widyastuti; Isti Haryati; Agus Pandoyo Muncar; Desi Ramadhani Siregar; Elis Ariesa Rani; Setya Novanta Wicaksana; Fauza Bulqois Lubis; Ni Luh Putu Cintya Heryanti; Beta Sari; Vita Diah Setyoningrum (Winaya Inspirasi Nusantara Foundation, 2024)
Sustainable heritage tourism increasingly depends on the capacity of local communities to act as effective cultural mediators, yet limited attention has been given to the role of foreign language competence as a mechanism of empowerment within heritage institutions. In many heritage destinations, tour guides are expected to communicate complex cultural meanings to international visitors, but insufficient linguistic resources may constrain their professional agency and the quality of heritage interpretation. This study aims to examine how foreign language capacity building functions as a form of community empowerment in a heritage tourism context, with specific reference to heritage tour guides at the Keraton Ngayogyakarta Hadiningrat, Indonesia. The study adopted a qualitative case study design. Data was collected through systematic observations of training sessions and guided tours, reflective discussions with participating guides, and analysis of training materials and institutional documents. The data were analyzed thematically, guided by empowerment theory and communicative competence theory. The findings indicate that foreign language training enhanced guides’ communicative confidence, interpretive depth, and intercultural awareness. Participants demonstrated greater flexibility in responding to visitor inquiries, improved narrative coherence in explaining cultural and historical meanings, and stronger perceptions of professional legitimacy as cultural representatives. While the training primarily supported psychological and social dimensions of empowerment, it contributed indirectly to cultural sustainability by strengthening heritage mediation practices. These findings suggest that foreign language capacity building has significant implications for sustainable heritage tourism and the operationalization of Sustainable Development Goal 11. Integrating language training into heritage management and community development initiatives can support more inclusive, high quality, and culturally grounded tourism practices.